Innovative applications of microalgae in biodegradable food packaging: A review - Samira Dakhili; Zahra Hashami; Negar Rostami; Samaneh Moradi; Maryam Moslehishad; Saeedeh Shojaee-Aliabadi (Journal of Agriculture and Food Research)
Edible films and coatings have gained prominence due to various factors such as environmental concerns, the growing issue of plastic waste disposal, the use of food industry by-products, and consumer demand for natural, nutritious, and healthy food options. Microalgae, single-celled photosynthetic microorganisms inhabiting aquatic environments, have the potential for the development of biodegradable and edible film and coating for packaging purposes. Functional and physicochemical properties of films and coatings incorporated with microalgae were investigated in this review. Incorporating microalgae leads to increased opacity and decreased lightness of the films. The moisture content, oxygen and water vapor permeability, solubility, mechanical properties, and structure of the films are also altered to some extent by the presence of microalgae. Additionally, the addition of microalgae biomass/extract to the matrix of the film and coating has exhibited antioxidant and antimicrobial activities, making it a potential natural preservative for seafood and meat and a means of extending the post-harvest shelf-life of fruits and vegetables, which could play a crucial role in marketing and exporting. This review highlights the direct use of various microalgae or their extracts in food packaging.